Beschreibung und Zucht von Ichneumon nebulosae spec. nov. Hymenoptera: Ichneumonidae). - Hinz, Rolf (Contributions to Entomology = Beiträge zur Entomologie, 1975)
Ichneumon nebulosae spec. nov. male and female is described.Nomenclatural Actsnebulosae Hinz, 1975 (Ichneumon), spec. n.